Energy integration of multiple-effect evaporator, thermo-vapor compressor, and background process. (15th October 2017) - Sharan, Prashant; Bandyopadhyay, Santanu
Abstract: Multiple-effect evaporators are commonly used in various industries such as food process, desalination, pulp and paper, etc. for increasing the liquor concentration. Multiple-effect evaporator is an energy intensive equipment. It is often integrated with various energy saving techniques for minimizing the energy consumption. A common technique is integration of multiple-effect evaporator with thermo-vapor compressor. In thermo-vapor compressor the low-pressure vapor produced in multiple-effect evaporator is compressed with the help of the high-pressure motive steam to produce an intermediate-pressure vapor, which in turn acts as a heat source for the multiple-effect evaporator. The optimal location of vapor suction position for thermo-vapor compressor can significantly affect the energy consumption of integrated multiple-effect evaporator and thermo-vapor compressor system. The other way of reducing the energy consumption is by integrating multiple-effect evaporator with the background process. The present work focuses on the development of a methodology to minimize the overall energy consumption by thermally integrating multiple-effect evaporator, thermo-vapor compressor, and the background process. A theorem for optimal location of vapor suction position for thermo-vapor compressor is proposed. Two examples are considered in this study for demonstrating the proposed methodology. An economic analysis is also carried out for calculating the cost benefit for the overall integration. Overall integration leads to 28% of energy saving and 22% reduction in annual cost for corn glucose example compared to standalone system. Similarly, for desalination example, 44% energy and 20% annual cost savings are observed. Graphical abstract: Highlights: Energy conservation in multiple-effect evaporator by integrating it with thermal systems. Optimal location of vapor suction position for thermo-vapor compressor. Energy efficiency for corn glucose improves by 28% in comparison to standalone system. Simultaneous reduction in energy consumption and annual cost for the integrated system.